Oil transport in surf zone - Cheng, Nian-Sheng (2012)
Oil transport subjected to nearshore currents in the surf zone is considered using the mass conservation equation. Analytical solutions are obtained that describe the longshore distribution of oil deposition, as well as the length of the shoreline contaminated by oil slicks transported in the nearshore environment. The solutions are related to the characteristic longshore and onshore velocities, which are evaluated separately, and oil-holding capacity of the shoreline. The analysis also shows that the distribution of oil deposition varies due to the re-entrainment. Sample computations for typical shoreline types are provided to illustrate the effect of oil-holding capacity. Finally, the Limitations of the analytical results are discussed.